DAMPAK ANGGARAN DANA KELURAHAN TERHADAP TINGKAT PENDAPATAN DAN KESEJAHTERAAN MASYARAKAT (STUDI KASUS PADA KELURAHAN KADOLOMOKO KOTA BAUBAU) - Adan, Laode Muhammad Hasrul; Fernando, Rahim (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study aims to determine the impact of the urban village budget on the construction of facilities and infrastructure as well as community empowerment activities in the Kadolomoko village and also to determine the impact of the village budget on the level of income and welfare of the people of the Kadolomoko village. The research method uses a qualitative descriptive analysis with a case study design. The population in this study were the village staff and the Kadolomoko village community, and the samples were the Kadolomoko village head, the Staff of the Head of the Economic Development and Welfare Section and three people from the Kadolomoko village community. Data collection techniques through interviews, observation and documentation. Based on the results of the research and data analysis, it was concluded: 1) The sub-district budget has an impact on the realization of facilities and infrastructure development activities and community empowerment in the Kadolomoko sub-district, even though the activities carried out have not met the expectations of the government and the Kadolomoko sub-district community as stated in the proposed musrembangkel for the 2020 Fiscal year; 2) The sub-district budget has an impact on increasing the income and welfare of the Kadolomoko sub-district community, the Kadolomoko sub-district community still gets benefits even though these benefits are not evenly distributed for each community